2015
DOI: 10.1186/1471-2253-15-17
|View full text |Cite
|
Sign up to set email alerts
|

Adequate sedation with single-dose dexmedetomidine in patients undergoing transurethral resection of the prostate with spinal anaesthesia: a dose–response study by age group

Abstract: BackgroundDexmedetomidine (DMT), a highly selective α2-adrenoceptor agonist, has been used safely as a sedative in patients under regional anesthesia. The purpose of this study was to determine the 50% effective dose (ED50) of single-dose DMT to induce adequate light sedation in elderly patients in comparison with younger patients undergoing transurethral resection of the prostate (TURP) with spinal anesthesia.MethodsForty-two male patients were recruited. The young age group (Group Y) included patients 45 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The adverse reactions included arrhythmia, tongue retraction, cough, agitation, hiccups, reflux and aspiration. Recovery time was measured using the Observer's Assessment of Alertness/Sedation scale (OAAS, Table 1 ) 7 , 8 . An OAAS score of 5 indicated rapid response to normal voice.…”
Section: Methodsmentioning
confidence: 99%
“…The adverse reactions included arrhythmia, tongue retraction, cough, agitation, hiccups, reflux and aspiration. Recovery time was measured using the Observer's Assessment of Alertness/Sedation scale (OAAS, Table 1 ) 7 , 8 . An OAAS score of 5 indicated rapid response to normal voice.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, dexmedetomidine, a selective α 2 -adrenoreceptor agonist, was a focus of interest for sedation during regional anesthesia due to its rapid offset, prolongation of spinal anesthesia, and excellent postoperative analgesia characteristics [ 3 , 4 ]. In addition, dexmedetomidine has a biphasic hemodynamic effect, whereby an initial increase in blood pressure by α 2 -receptor-mediated peripheral vasoconstriction is followed by a decrease due to norepinephrine release and sympathetic activity inhibition in central nervous system [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al13 reported that the single dose of DEX required for sedation was 21% lower in older men (65–78 years old) compared to younger men (45–64 years old) who underwent transurethral resection of the prostate with spinal anesthesia. Our results show that among patients who underwent dental surgery under local anesthesia, the single dose of DEX required for sedation was 22.5% lower in the group aged 80 years and older compared to the group aged 70 to 74 years.…”
Section: Discussionmentioning
confidence: 99%